5-hydroxytryptamine release into human jejunum by cholera toxin. Issue 4 (October 1996) - Bearcroft, C P; Perrett, D; Farthing, M J
Abstract : BACKGROUND: Cholera toxin produces intestinal secretion by activation of the adenylate cyclase complex. However animal studies have shown 5-hydroxytryptamine may be released after exposure to cholera toxin, and thereby contribute to the secretory state. AIM: To determine whether cholera toxin releases 5-hydroxytryptamine in human jejunum. SUBJECTS: Seven male subjects were given a subclinical dose of cholera toxin in a paired, controlled, randomised, double blind study. METHODS: A closed 10 cm segment of upper jejunum was exposed to 15 micrograms of cholera toxin for two hours prior to closed segment perfusion with plasma electrolyte solution containing a non-absorbable volume marker, [14C]-polyethylene glycol. 5-Hydroxytryptamine in jejunal effluent and 5-hydroxyindoleacetic acid in urine (up to seven hours after cholera toxin) were measured by high performance liquid chromatography with fluorimetric detection. RESULTS: In contrast with controls, all subjects secreted fluid in response to cholera toxin, median-2.1 ml/cm/h (interquartile range-4.1 to -0.1). During seven hours following cholera toxin, 5-hydroxytryptamine was secreted into the lumen (range 31 to 395 nmol/l) but not in control experiments. After exposure to cholera toxin median urinary 5-hydroxyindoleacetic acid was 5.7 (4.1 to 6.3), which was similar to controls 4.9 (4.1 to 6.3), which was similar to controls 4.9 (4.1 to 6.2). CONCLUSION: Thus, cholera toxin induced a secretory state and promoted the release of 5-hydroxytryptamine into the intestinal lumen, but quantitative changes in urinary 5-hydroxyindoleacetic acid were not detectable. As an intestinal secretagogue, these findings suggest that 5-hydroxytryptamine may play a part in mediating cholera toxin induced secretion in humans.